Use of alternative payment models for substance use disorder prevention in the United States: development of a conceptual framework - Elian Rosenfeld; Sarah Potter; Jennifer Caputo; Sushmita Shoma Ghose; Nelia Nadal; Christopher M. Jones; Margaret R. Kuklinski; Andrew D. Carlo; D. Max Crowley; Lisa Clemans-Cope; Michael T. French (Substance Abuse Treatment, Prevention, and Policy)
Abstract Background Alternative payment models (APMs) are methods through which insurers reimburse health care providers and are widely used to improve the quality and value of health care. While there is a growing movement to utilize APMs for substance use disorder (SUD) treatment services, they have rarely included SUD prevention strategies. Challenges to using APMs for SUD prevention include underdeveloped program outcome measures, inadequate SUD prevention funding, and lack of clarity regarding what prevention strategies might fit within the scope of APMs. Methods In November 2023, the Substance Abuse and Mental Health Services Administration (SAMHSA), through a contract with Westat, convened an expert panel to refine a preliminary conceptual framework developed for utilizing APMs for SUD prevention and to identify strategies to encourage their adoption. Results The conceptual framework agreed upon by the panel provides expert consensus on how APMs could finance a variety of prevention programs across diverse populations and settings. Additional efforts are needed to accelerate the support for and adoption of APMs for SUD prevention, and the principles of health equity and community engagement should underpin these efforts. Opportunities to increase the use of APMs for SUD prevention include educating key groups, expanding and promoting the SUD prevention workforce, establishing funding for pilot studies, identifying evidence-based core components of SUD prevention, analyzing the cost effectiveness of APMs for SUD prevention, and aligning funding across federal agencies. Conclusion Given that the use of APMs for SUD prevention is a new practice, additional research, education, and resources are needed. The conceptual framework and strategies generated by the expert panel offer a path for future research. SUD health care stakeholders should consider ways that SUD prevention can be effectively and equitably implemented within APMs.